2011
DOI: 10.1007/s10439-011-0339-9
|View full text |Cite
|
Sign up to set email alerts
|

Body-Worn Sensor Design: What Do Patients and Clinicians Want?

Abstract: User preferences need to be taken into account in order to be able to design devices that will gain acceptance both in a clinical and home setting. Sensor systems become redundant if patients or clinicians do not want to work with them. The aim of this systematic review was to determine both patients' and clinicians' preferences for non-invasive body-worn sensor systems. A search for relevant articles and conference proceedings was performed using MEDLINE, EMBASE, Current Contents Connect, and EEEI explore. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
163
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(168 citation statements)
references
References 31 publications
4
163
1
Order By: Relevance
“…We chose to investigate temperature and SMEG because they are the most commonly used biofeedback modalities [11], and are shown to be especially effective in adolescents [31]. We identified sensors fulfilling a set of predefined criteria considered necessary for the sensor to gain acceptance among patients, and thus be used [32]. The choice of sensors was arbitrary as long as the predefined criteria were met.…”
Section: Principal Findingsmentioning
confidence: 99%
“…We chose to investigate temperature and SMEG because they are the most commonly used biofeedback modalities [11], and are shown to be especially effective in adolescents [31]. We identified sensors fulfilling a set of predefined criteria considered necessary for the sensor to gain acceptance among patients, and thus be used [32]. The choice of sensors was arbitrary as long as the predefined criteria were met.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Sensor systems rapidly become redundant if patients or clinicians do not want to work with them. A review of patients' and clinicians' preferences for non-invasive, body-worn sensor systems found that a body-worn sensor system should be compact, embedded, simple to operate, and should not affect daily behavior nor seek to directly replace a healthcare professional [46]. Therefore, wearable chemical sensors should be seen as an additional tool to assist in healthcare delivery and to provide better continuity of care.…”
Section: Interface With the Bodymentioning
confidence: 99%
“…Although system wearability is subjective, users generally prefer that BSNs are compact, embedded on the body, and do not affect their daily behavior [3]. Therefore, system wearability can be optimized by designing a BSN to have these qualities.…”
Section: B System Wearability Optimizationmentioning
confidence: 99%
“…To address user acceptance, researchers have emphasized the importance of making BSNs wearable and wireless [3]. To address battery life, researchers have emphasized the importance of making BSNs ultra-low power so that they can operate for long periods of time on a small battery or even be powered by an energy harvester attached to the body [4].…”
Section: Introductionmentioning
confidence: 99%